Efficacy of Shenglin decoction in preventing acute severe lymphocytopenia in patients with non-small cell lung cancer undergoing concurrent chemoradiotherapy: a study protocol for a randomized controlled trial - Deng, Jiayao; Gong, Cuicui; Xiao, Qi; Xu, Bo; Li, Huakang; Wu, Ziliang; Xiao, Qian; Gu, Pengxuan; Li, Qiang; Li, Bin; Wang, Yue; Lin, Bing; et al. (Frontiers in Oncology, 2024)
Background: Definitive concurrent chemoradiotherapy (CCRT) followed by maintenance therapy with immune checkpoint inhibitors offers the best chance of cure for patients with stage III non-small cell lung cancer (NSCLC). A significant challenge in this regimen is the occurrence of acute severe lymphopenia (ASL), which can compromise treatment efficacy. Currently, there are no effective strategies for preventing and treating ASL. Shenglin decoction (SLD), a traditional Chinese herbal medicine formulation, has demonstrated preliminary efficacy in mitigating ASL.However, robust evidence from clinical trials and a clear understanding of its mechanism of action are still needed. This study aims to comprehensively assess the efficacy, safety, and underlying mechanisms of SLD in the prevention of ASL.Methods: This prospective, dual-center, open-label, randomized controlled trial will enroll 140 stage III NSCLC patients. Participants will be randomly allocated in a 1:1 ratio to a control group or an experimental group. Both groups will undergo definitive CCRT. Alongside the commencement of CCRT, the experimental group will receive an additional oral SLD intervention for a duration of three months. The primary outcome is the incidence rate of ASL, defined as the proportion of patients who experience at least one instance of a total lymphocyte count falling below 0.5 × 10^9 cells/L within 3 months of initiating CCRT treatment. Additionally, 16S rRNA gene sequencing analysis of fecal samples to assess gut microbiota, as well as metabolomic analysis of fecal/blood samples, will be conducted to explore potential mechanisms.Discussion: This study protocol aims to rigorously evaluate the efficacy and safety of SLD, as well as elucidate its mechanism of action in preventing ASL. Successful outcomes could establish SLD as an evidence-based intervention for ASL prevention in NSCLC patients undergoing CCRT.Trial Registration: The trial was registered at the Chinese Clinical Trials Registry (ChiCTR2300071788, https://www.chictr.org.cn/)